Characterization of volcanic deposits and geoarchaeological studies from the 1815 eruption of Tambora volcano - Igan Supriatman Sutawidjaja; Haraldur Sigurdsson; Lewis Abrams (Indonesian Journal on Geoscience, 2006)
http://dx.doi.org/10.17014/ijog.vol1no1.20066aThe eruption of Tambora volcano on the island of Sumbawa in 1815 is generally considered as the largest and the most violent volcanic event in recorded history. The cataclysmic eruption occurred on 11 April 1815 was initiated by Plinian eruption type on 5 April and killed more than 90,000 people on Sumbawa and nearby Lombok. The type plinian eruptions occurred twice and ejected gray pumice and ash, to form stratified deposits as thick as 40-150 cm on the slopes and mostly distributed over the district west of the volcano. Following this, at about 7 pm, on 11 April the first pyroclastic surge was generated and progressively became greater extending to almost whole direction, mainly to the north, west, and south districts from the eruption center. The deadliest volcanic eruption buried ancient villages by pyroclastic surge and flow deposits in almost intact state, thus preserving important archaeological evidence for the period. High preservation in relatively stable conditions and known date of the eruptions provide approximate dating for the archaeological remains. Archaeological excavations on the site uncovered a variety of remains were relieved by ground penetrating radar (GPR) to map structural remains of the ancient villages under the pyroclastic surge and flow deposits. These traverses showed that GPR could define structures as deep as 10 m (velocity 0.090 m/ns) and could accurately map the thickness of the stratified volcanic deposits in the Tambora village area.